Penerapan Sistem Informasi Akuntansi Dan Sistem Pengendalian Internal Terhadap Kualitas Laporan Keuangan Pada Bpr Se-Kecamatan Mengwi - I Gusti Ayu Made Ira Sasmita; I Dewa Ayu Kristiantari; I Dewa Ayu Eka Pertiwi (Program Studi Akuntansi, Fakultas Ekonomi, Universitas Warmadewa, 2026)
This study aims to thoroughly examine the impact of the implementation of accounting information systems and the effectiveness of internal control systems on the quality of financial reporting at Rural Banks (BPR) in the Mengwi District. The approach employed is quantitative, involving 98 individuals as respondents. The data analysis techniques used include Multiple Linear Regression, along with F-test and t-test statistical methods. Empirical findings indicate that the accounting information system contributes positively and significantly to improving the quality of financial statements, as does the internal control system. The practical implications of these results encourage BPR management to conduct regular training focused on enhancing employees’ technical competencies in operating the accounting information system. In addition, continuous system updates are necessary to ensure adaptability to regulatory dynamics and operational needs. On the other hand, strengthening internal control is recommended through structured procedure updates, optimization of monitoring mechanisms, and clear separation of functions between units to minimize the risk of errors and irregularities.